Cholinesterase activities in cerebrospinal fluid of patients with senile dementia of Alzheimer type. - Appleyard, M; Smith, A; Berman, P; Wilcock, G; Esiri, M; Neary, D; Bowen, D (1987)
Acetylcholinesterase (AChE) and nonspecific cholinesterase (nsChE) activities of lumbar ceresbrospinal fluid (CSF) from patients with a clinical or histological diagnosis of Alzheimer's disease have been compared with those of normal age-matched control patients and patients with dementia of non-Alzheimer aetiology. No significant differences in the AChE activity of lumbar CSF from histologically and clinically diagnosed Alzheimer's disease patients and normal age-matched controls were found, although they could be distinguished from controls and other dements by their lower lumbar CSF levels of nsChE activity and by their elevated ratio of AChE/nsChE. A lower level of AChE activity was observed in the lumbar CSF of patients with dementia of non-Alzheimer aetiology. The AChE and nsChE activities of ventricular CSF obtained at postmortem have also been examined. The AChE activity of the ventricular CSF of patients with histologically confirmed Alzheimer's disease was 66% lower than that of age-matched controls; these patients could also be distinguished from normals by their lower levels of nsChE and by the elevated ratio of AChE/nsChE activities. A molecular defect in the AChE in the ventricular CSF of Alzheimer patients is indicated by the finding that the enzyme failed to show inhibition by high concentrations of substrate. The lower level of AChE in ventricular CSF may reflect the changes in this enzyme in forebrain regions of Alzheimer patients. Although it is at present not possible to correlate the lower levels of nsChE found in CSF with any known brain pathology, the significantly altered ratio of AChE/nsChE activities in lumbar CSF may possibly form the basis for a diagnostic test of Alzheimer type dementia.